Tyro3 and Gas6 are associated with white matter and myelin integrity in multiple sclerosis - Igal Rosenstein; Lenka Novakova; Hlin Kvartsberg; Anna Nordin; Sofia Rasch; Elzbieta Rembeza; Sofia Sandgren; Clas Malmeström; Stefanie Fruhwürth; Markus Axelsson; Kaj Blennow; Henrik Zetterberg; et al. (Journal of Neuroinflammation)
Abstract Background The Gas6/TAM (Tyro3, Axl, and Mer) receptor system has been implicated in demyelination and delayed remyelination in experimental animal models, but data in humans are scarce. We aimed to investigate the role of Gas6/TAM in neurodegenerative processes in multiple sclerosis (MS). Methods From a prospective 5-year follow-up study, soluble Gas6/TAM biomarkers were analyzed in cerebrospinal fluid (CSF) by enzyme-linked immunosorbent assay (ELISA) at baseline in patients with relapsing–remitting MS (RRMS) (n = 40), progressive MS (PMS) (n = 20), and healthy controls (HC) (n = 25). Brain volumes, including myelin content (MyC) and white matter (WM) were measured by synthetic magnetic resonance imaging at baseline, 12 months, and 60-month follow-up. Associations with brain volume changes were investigated in multivariable linear regression models. Gas6/TAM concentrations were also determined at 12 months follow-up in RRMS to assess treatment response. Results Baseline concentrations of Tyro3, Axl, and Gas6 were significantly higher in PMS vs. RRMS and HC. Mer was higher in PMS vs. HC. Tyro3 and Gas6 were associated with reduced WM (β = 25.5, 95% confidence interval [CI] [6.11–44.96, p = 0.012; β = 11.4, 95% CI [0.42–22.4], p = 0.042, respectively) and MyC (β = 7.95, 95%CI [1.84–14.07], p = 0.012; β = 4.4, 95%CI [1.04–7.75], p = 0.012 respectively) at 60 months. Patients with evidence of remyelination at last follow-up had lower baseline soluble Tyro3 (p = 0.033) and Gas6 (p = 0.014). Except Mer, Gas6/TAM concentrations did not change with treatment in RRMS. Discussion Our data indicate a potential role for the Gas6/TAM receptor system in neurodegenerative processes influencing demyelination and ineffective remyelination.